The Overview of Natural by-Products of Beneficial Lactic Acid Bacteria as Promising Antimicrobial Agents - Fugaban, Joanna Ivy Irorita; Holzapfel, Wilhelm Heinrich; Todorov, Svetoslav (Applied Food Biotechnology, 2022)
Background and Objective: Aside from ability of lactic acid bacteria to conduct fermentation process, by transforming the raw materials into the final food products, they play an essential role in preservation and also production of distinct food flavors through biotransformation of organic acids and compounds. Functionality of lactic acid bacteria has been associated with their ability to produce a wide array of antimicrobial compounds which acts as a gatekeeper for the integrity of food products and safety for the consumers. Bio-preservation properties of lactic acid bacteria is associated to the production of antimicrobial peptides (including bacteriocins), variety of organic acids, diacetyl, reuterin, low molecular organic metabolites, hydrogen peroxide, and carbon dioxide, among many others. Different antimicrobials play an essential role not only in the bio-preservation, based on their antibacterial properties, but can be key factors in the anti-mould and consequently reducing the mycotoxins and/or enhance probiotic properties when lactic acid bacteria were applied as. In this review, we aim to present this in a structured manner with different examples for the application of lactic acid bacteria and their antimicrobials metabolites in bio-preservation and medical sector versus bacterial and molds and as part of the probiotics properties. Results and Conclusion: Lactic acid bacteria are powerful microbial factories, which are able to conduct different fermentation process, to produce variety of beneficial metabolites not just for food biosafety but also for beneficial properties of probiotics and their health promoting properties. Conflict of interest: The authors declare no conflict of interest.